PENGARUH KETIDAKPASTIAN LINGKUNGAN DAN BUDAYA ORGANISASI TERHADAP PARTISIPASI PENGANGGARAN DAN KINERJA MANAJERIAL - DEASY RINARTI; MUINDRO RENYOWIJOYO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2007)
In several prior researchs, that examined and proved relationship between budgetary participation and managerial performance, have yield the inconsistency results. The inconsistency results may reflect the influence of contingency variables. This study include an environmental uncertainty and organization culture as moderating variables in relationship between budgetary participation and managerial performance, could solve the differences. Data for this study were collected by using quesionaires, which were mailed to 150 travel managers. There were 88 responses of which 84 were completed and used. The result indicates that there was a significantly positif relation-ship between budgetary participation and managerial performance. The result from this study indicated that organization culture moderate the relationship between budgetary participation and managerial performance. But environmental uncertainty doesn’t moderate the relationship between budgetary participation and managerial performance.